Analyzing land use changes and wetland dynamics: Muthurajawela urban wetland and its surroundings, Sri Lanka - Dahanayake, Harsha Dias; Dahanayaka, DDGL; Hudson, Paul; Wickramasinghe, Deepthi (Brawijaya University, 2024)
Land Use and Land Cover changes (LULC) exert a substantial influence on human life and environmental well-being. This research utilized the Intensity Analysis (IA) method to assess LULC change intensities spanning from 2000 to 2021 in the Muthurajawela coastal wetland (MW) and its 5km buffer zone (MB) along the west coast of Sri Lanka. The research employed Landsat Thematic Mapper (TM) and Optical Land Imager (OLI) Remote Sensing Images. The supervised classification was used to accurately identify waterbodies, thick vegetation, other vegetation, settlements, and open areas with an average of 86% accuracy. The study revealed that the MW experienced a fast Interval level intensity shift during 2000-2010, followed by a slower pace during 2010-2021. Conversely, the MB displayed a consistently fast Interval level intensity throughout both time intervals. Notably, waterbodies in MW decreased by 19.6%, while settlements witnessed a gain of 19.1% over the entire period. Transition Level (TL) analyses underscored the transformation of water bodies to open areas (6.75% in 2000-2010) and open areas to settlements (5.38%). In MB, other vegetation saw a significant decrease of 33.7%, with settlements registering a notable increase of 39.4% over the entire period. The study emphasizes urgent action for sustainable land use development in the face of rapid urbanization within the study area.